Transwomen and the Prison Industrial Complex - Masikini, Naciza (2016)
As one of the fastest growing populations in the prison system, transwomen have a unique relationship with the prison system and the Prison Industrial Complex. These systems work to further the marginalization of transwomen by subjecting them to psychological and sexual violence. Transwomen’s bodies are criminalized in ways that naturalizes the violence they experience both in the prisons and in the court systems. This paper aims to provide an overview of the ways in which transwomen are dehumanized in their encounters with the criminal justice system (i.e. mis-gendering, the physical and sexual abuse they experience) by contextualizing their experiences. Through contextualization, I aim to illustrate the interlocking systems of oppression that construct transwomen as socially deviant bodies, that leads to their encounters with the Prison Industrial Complex. Additionally, I explore how these interlocking systems of oppression continue to function within the context of the Prison Industrial Complex and how that reduces transwomen to Agamben’s conceptualization of bare life and as ‘non- citizens’ within the carceral state